2018
DOI: 10.1111/joor.12702
|View full text |Cite
|
Sign up to set email alerts
|

Immediate loading at single crowns and 2‐unit bridges supported by implants installed in a healed alveolar bony ridge or immediately after tooth extraction. An experimental study in dogs

Abstract: To evaluate presumptive differences in osseointegration at implants installed in healed sites or extraction sockets, supporting either crowns or bridges that were functionally loaded or left unloaded. In six dogs, the mesial roots of the first mandibular molars were treated endodontically. Bilaterally, the teeth were hemisected, and the distal roots extracted. First and second mandibular premolars were extracted as well. After 3 months, the mandibular third and fourth distal roots were extracted after endodont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Survival was de ned as implants remaining in situ during the follow-up period. Only Han et al 25 , Atieh et al 29 and Vigano et al 27 reported RFA values that is ≥70 (95% CI: 77.8-80.3); 76.63 ± 10.65 and 53.8-70.8, respectively. The implant success rate in Atieh et al 29 research was evaluated according to the criteria by Albrektsson & Zarb.…”
Section: Implant Survial Ratementioning
confidence: 99%
See 3 more Smart Citations
“…Survival was de ned as implants remaining in situ during the follow-up period. Only Han et al 25 , Atieh et al 29 and Vigano et al 27 reported RFA values that is ≥70 (95% CI: 77.8-80.3); 76.63 ± 10.65 and 53.8-70.8, respectively. The implant success rate in Atieh et al 29 research was evaluated according to the criteria by Albrektsson & Zarb.…”
Section: Implant Survial Ratementioning
confidence: 99%
“…Two articles were of the animal studies. 27,28 The rest of 8 studies were the controlled clinical trials. 25,26,[29][30][31][32][33] The age range of patients included in these studies was from 15 to 83 years.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations